PENGARUH KOMPENSASI, PELATIHAN DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DINAS PERIKANAN KOTA TANJUNGBALAI - Muhammad Husin; Desfi Marlisa Nasution; M. Fazlur Rahman Daulay; Novi Afriani; Robert Arozatulo Zebua (Manajemen dan Bisnis, 2021)
The formulation of the problem in this study is: How does compensation, training and work motivation  influence  the work productivity  at Dinas Perikanan  Kota Tanjungbalai. This study aims to determine the effect of compensation, training and  work  motivation  on  employee  work  productivity.   With  total  sampling technique,   the  sample   in  this  study   was  41  people.   The  results  showed; Compensation  partially  has  a  positive  effect  on  employee  work  productivity; Partial training has a positive effect on employee work productivity; Work motivation partially has a positive influence on employee work productivity; Training, compensation and work motivation simultaneously have a positive and significant effect on employee work productivity.